Calculation of G Gravity Constant from the Mass, Electron Charge and the Fine Structure Constant: A Theoretical Point of View - Valentino Straser; Fernand Leon Van Rutten (New Trends in Physical Science Research Vol. 5, 2022)
This paper proposes, from a theoretical standpoint, the calculation of the gravitational constant G, made starting from the charge and from the electron mass, while also considering the Fine Structure constant.. In the empty space, couples of virtual positron electrons dematerialize, being to give rise to virtual photons. They, at their time, will become electrons, positrons and so on. These alterations are carried out while keeping track of their "amount of movement," and when they encounter matter, these couples emerge, republished according to the field and the mass of matter. The issue is a shift in their gyromagnetic movement relationship, which puts them under pressure. In presence of two masses, the change in the trend of the gyromagnetic ratio causes one of the two masses to be partially oriented toward the other. From here a force is established between these two masses that gives as calculated constant equal to 6.678720706E-11. This value of G, calculated from the charge and electron mass, is quite close to the experimental values established in recent decades for the gravitational constant of G.